APETALA2/ethylene responsive factor in fruit ripening: Roles, interactions and expression regulation - Zhai, Yanlei; Fan, Zhiyi; Cui, Yuanyuan; Gu, Xiaojiao; Chen, Shangwu; Ma, Huiqin (Frontiers in Plant Science, 2022)
Insects and animals are attracted to, and feed on ripe fruit, thereby promoting seed dispersal. As a vital vitamin and nutrient source, fruit make up an indispensable and enjoyable component of the human diet. Fruit ripening involves a series of physiological and biochemical changes in, among others, pigmentation, chlorophyll degradation, texture, sugar accumulation and flavor. Growing evidence indicates that the coordinated and ordered trait changes during fruit ripening depend on a complex regulatory network consisting of transcription factors, co-regulators, hormonal signals, and epigenetic modifications. As one of the predominant transcription factor families in plants and a downstream component of ethylene signaling, more and more studies are showing that APETALA2/ETHYLENE RESPONSIVE FACTOR (AP2/ERF) family transcription factors act as critical regulators in fruit ripening. In this review, we focus on the regulatory mechanisms of AP2/ERFs in fruit ripening, and in particular the recent results on their target genes and co-regulators. We summarize and discuss the role of AP2/ERFs in the formation of key fruit-ripening attributes, the enactment of their regulatory mechanisms by interaction with other proteins, their role in the orchestration of phytohormone-signaling networks, and the epigenetic modifications associated with their gene expression. Our aim is to provide a multidimensional perspective on the regulatory mechanisms of AP2/ERFs in fruit ripening, and a reference for understanding and furthering research on the roles of AP2/ERF in fruit ripening.